Contexts, applications and innovation in the official documents of SED/SC: New proposal for innovative teaching in philosophy (Research, Society and Development, 2021)
The article addresses the notion of innovation in scientific literature and in official documents prepared by the Department of Education, of the State of Santa Catarina – SED/SC, with special emphasis on innovation in the teaching of Philosophy. It seeks to understand in the curriculum proposals the different contexts and applications of the concept of innovation. The teaching documents and notebooks presented by the new integral and innovative teaching models are analyzed. The main gaps in traditional education are identified, in search of a balance and the creation of conditions for an innovative process in education. Innovation and entrepreneurship in high school enable changes in the school environment, in pedagogical relationships and in the teaching and learning process, and qualify young people for life and work. Innovation involves interdisciplinary practice, teacher creativity and inventiveness in methodological terms and teaching strategies, new curriculum design, school management, pedagogical planning, use of technologies, new assessment models, together with the entrepreneurship of institutions, stimulated by the State, as responsible for educational policies.